HOLISTIC PERFORMANCE ASSESSMENT AS AN INSTRUMENT FOR EMPLOYEE COMPETENCY DEVELOPMENT IN PUBLIC ELEMENTARY SCHOOLS: Asesmen Kinerja Holistik sebagai Instrumen Pengembangan Kompetensi Pegawai di Sekolah Dasar Negeri - Darsono; Yuni Pantiwati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Holistic performance assessment is an assessment approach that focuses not only on work outcomes, but also on the process, potential, and personality and social aspects of employees in the context of basic education. This study aims to analyze the application of holistic performance assessment as an instrument for employee competency development at SDN Rampal Celaket 1 Malang City. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation of school principals, teachers, and education staff. The results of the study show that holistic performance assessment is able to provide a comprehensive picture of employee performance through the integration of cognitive, affective, and psychomotor aspects. The application of this assessment contributes to the improvement of employees' professional, pedagogic, social, and personality competencies through reflective feedback and continuous development planning. In addition, the assessment process involving active participation between assessors and employees encourages a collaborative, transparent, and work-oriented work culture that is oriented towards improving the quality of educational services. The main obstacle found is the limited understanding and consistency of the implementation of assessments in the field, so continuous training and assistance are needed for schools. Thus, holistic performance assessment can be used as a strategic instrument in educational human resource management to build adaptive, reflective, and competitive employee competencies, in line with the demands of 21st century education transformation.